Effect of a Tea Polyphenol on Different Levels of Exposure of Nicotine and Tobacco Extract on Streptococcus mutans Biofilm Formation - Taylor, Emily S.; Gomez, Grace F.; Moser, Elizabeth A. S.; Sanders, Brian J.; Gregory, Richard L. (Frontiers in Oral Health, 2021)
Objective: The purpose of this study was to compare the effects of different levels of nicotine and tobacco extract exposure on Streptococcus mutans biofilm formation and the inhibitory effect of the polyphenol epigallocatechin-3 gallate (EGCG) found in green tea. This study addressed the results of biofilm assays with EGCG and varying relative concentrations of nicotine and tobacco extract consistent with primary, secondary and tertiary levels of smoking exposure. Primary smoking exposure to nicotine has been demonstrated to significantly increase biofilm formation, while EGCG has been demonstrated to reduce S. mutans biofilm formation. Methods:S. mutans was treated with varying levels of nicotine or cigarette smoke condensate (CSC) concentrations (0–32 mg/ml and 0–2 mg/ml, respectively) in Tryptic Soy broth supplemented with 1% sucrose for different lengths of time simulating primary, secondary and tertiary smoking exposure with and without 0.25 mg/ml EGCG. The amount of total growth and biofilm formed was determined using a spectrophotometric crystal violet dye staining assay. Results: For both nicotine and CSC, primary exposure displayed overall significantly less growth compared to secondary exposure. For nicotine, secondary exposure demonstrated significantly greater growth than tertiary exposure levels. Overall, significantly greater total bacterial growth and biofilm formation in the presence of nicotine and CSC was observed in the absence of EGCG than in the presence of EGCG. However, biofilm growth was not significantly different among different concentrations of CSC. Conclusion: The results of this study help illustrate that nicotine-induced S. mutans biofilm formation is reduced by the presence of EGCG. This provides further evidence of the potential beneficial properties of polyphenols.